2006
DOI: 10.1038/nature04768
|View full text |Cite|
|
Sign up to set email alerts
|

Systems biology approaches identify ATF3 as a negative regulator of Toll-like receptor 4

Abstract: The innate immune system is absolutely required for host defence, but, uncontrolled, it leads to inflammatory disease. This control is mediated, in part, by cytokines that are secreted by macrophages. Immune regulation is extraordinarily complex, and can be best investigated with systems approaches (that is, using computational tools to predict regulatory networks arising from global, high-throughput data sets). Here we use cluster analysis of a comprehensive set of transcriptomic data derived from Toll-like r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

38
763
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 734 publications
(825 citation statements)
references
References 25 publications
38
763
2
Order By: Relevance
“…27 TLR signaling represents one of the key mechanisms involved in these processes. 28 Although ATF3, an ATF4 homologue, has been reported to participate in the TLR4 signaling pathway 8,29 and recent reports have indicated that ATF4 is capable of regulating cytokine secretion, 9 it remains unclear whether ATF4 plays a role in TLR signaling. In this study, we defined a novel mechanism in which ATF4 is recruited by TLR4 signaling via the MyD88-dependent pathway, translocates to the nucleus and stimulates TLR-triggered cytokine production to further promote an inflammatory reaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 TLR signaling represents one of the key mechanisms involved in these processes. 28 Although ATF3, an ATF4 homologue, has been reported to participate in the TLR4 signaling pathway 8,29 and recent reports have indicated that ATF4 is capable of regulating cytokine secretion, 9 it remains unclear whether ATF4 plays a role in TLR signaling. In this study, we defined a novel mechanism in which ATF4 is recruited by TLR4 signaling via the MyD88-dependent pathway, translocates to the nucleus and stimulates TLR-triggered cytokine production to further promote an inflammatory reaction.…”
Section: Discussionmentioning
confidence: 99%
“…First, an ATF4 homologous molecule, ATF3, is an important negative regulator of the TLR4 signaling pathway. 8 Second, TLR ligand stimulation causes macrophages to secrete high levels of IL-8, while ATF4 positively regulates IL-8 secretion in the same type of cells. 9,10 In this study, we demonstrated that ATF4 participates in the TLR4 signaling pathway and positively regulates TLR4-triggered cytokine production.…”
Section: Introductionmentioning
confidence: 99%
“…Many of the TLR bind lipid structures. Thus it can be expected that the advances made in the systems biology of TLRs [23], and chemical analysis of naturally occurring forms of LPS [24] will bring together knowledge from different fields in order to understand better the molecular mechanisms of pathogen recognition.…”
Section: Pathogenic Bacteria (Mycobacteria Salmonella)mentioning
confidence: 99%
“…TLR4 activates nuclear factor-kB on which concomitant activation of activating transcription factor 3 (ATF3) has been proposed to give a negative feedback (Gilchrist et al, 2006). TLR4 knockout mice display pulmonary emphysema at high age (Zhang et al, 2006).…”
Section: Introductionmentioning
confidence: 99%